The Relations Between Moldova and the EU in 1998 – 2012 - V. B. Kirillov; I. S. Putintsev (Vestnik MGIMO-Universiteta)
The article reviews the relations between Moldova and the EU at the current stage. Reasons for the strengthening of cooperation between Moldova and the EU in these years are being analyzed, as well as the problems that further development of cooperation can face. It is described how relations with the EU influence the prospects of Moldova’s participation in the integration process in the post- Soviet space.